Socialization of Food Safety and Halal Certification for Culinary Merchants at Griya Kuliner Bundaran Pacet - Sri Handajani; Nugrahani Astuti; Ratna Palupi Nurfatimah; Febriani Lukitasari; Rendra Lebdoyono; Asrul Bahar; Siti Yuliana (Universitas Pendidikan Ganesha, 2025)
This The low level of understanding of culinary merchants in Griya Kuliner Bunderan Pacet (GriaKu) regarding food safety and Halal certification is the main focus of this Community Service Program. This problem has an impact on the quality of products sold and consumer trust in the Halal and safety of food to be consumed. The main objective of this program is to strengthen the understanding of culinary merchants in GriaKu Bunderan Pacet regarding the importance of implementing food safety and halal certification, so that it can help them maintain product quality and provide halal assurance to consumers. The type of research used in this program is qualitative research with a participatory approach. The subjects involved in this study were culinary merchants in GriaKu Bunderan Pacet. The data collection method from this activity includes a series of socializations with an approach involving direct observation, in-depth interviews, and focus group discussions (FGD). This program successfully identified various problems faced by merchants and formulated relevant solutions. The results of this activity showed a significant increase in merchants’ awareness and understanding of the importance of maintaining cleanliness, food safety, and halal certification procedures, how to maintain them. This program is also expected to provide long-term impacts, namely improving the quality of products sold and supporting the sustainability of culinary businesses in the region through responsible practices.